CHALLENGES FOR THE PEDAGOGIST IN EDUCATIONAL SUPERVISION - Bartinelly Sousa da Silva Melo, Sílvia (Revista Gênero e Interdisciplinaridade, 2023)
Brazilian education has been the scene of great discussions and contradictions, as it influences and is influenced by the ascending transformations that have occurred in society; and, while, more and more, qualification and educational preparation are demanded and “money” is invested in the education system. In this context, the role of the pedagogue proves to be fundamental, and he, despite being in the middle of a “crossfire”, must seek to play his role in a much more comprehensive way, being essentially concerned with the educational supervision itself. , guiding, advising, prioritizing the educational collective and the promotion of critical, participatory citizens who transform their reality. From this perspective, the referred work focuses as a basic objective to point out how the pedagogue has been playing its role within the educational supervision; establishing for the accomplishment of this intention, studies of theoretical order, as well as observations in the routine of the daily work. It is concluded that the pedagogue suffers many restrictions that end up interfering with the work done and oblige him to unfold to perform his social function and promote a quality education. In line with the information acquired throughout the work, at the end some considerations are established, through which it is intended to help other research that may be triggered.